Digital Representations of Student Performance for Assessment
VIII, 216 p.
Keywords: It was the belief that assessment is the driving force of curriculum that motivated the authors of this monograph to embark on a program of research and development into the use of digital technologies to support more authentic forms of assessment. They perceived that in responding to the educational needs of children in the 21st Century, curriculum needed to become more relevant and engaging, but that change was unlikely without commensurate change in methods and forms of assessment. This was particularly true for the high-stakes assessment typically conducted at the conclusion of schooling as this tended to become the focus of the implemented curriculum throughout the years of school. Therefore the authors chose to focus on this area of assessment with the understanding that this would inform assessment policy and practices generally in schools. This book provides a conceptual framework and outlines a project in which digital methods of representing students performance were developed and tested in the subject areas of Applied Information Technology, Engineering, Italian and Physical Education. The methodology and data collection processes are discussed, and the data is analysed, providing the basis for conclusions and recommendations.